213k views
5 votes
Let f(x)=4^x. The new function g(x)=f(x-1)+3 represents transformations that were made to function f.

Write the new equation for g.
G=

1 Answer

2 votes

Answer:


g(x) = 4^(x-1) + 3

Explanation:

Given


f(x) = 4^x


g(x) = f(x-1) + 3

Required

Determine g(x)

First, we need to calculate f(x-1)

Given that:


f(x) = 4^x

Subtract 1 from x


f(x-1) = 4^(x-1)

Add 3 to both sides


f(x-1) + 3 = 4^(x-1) + 3

Recall that:


g(x) = f(x-1) + 3

This implies that:


g(x) = 4^(x-1) + 3

User Unn
by
6.0k points